2007
DOI: 10.1021/jp075605x
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light Induced Photoelectrochemical Properties of n-BiVO4and n-BiVO4/p-Co3O4

Abstract: The visible light induced photoelectrochemical properties of the pressed powder electrodes n-BiVO 4 , p-Co 3 O 4 , and n-BiVO 4 /p-Co 3 O 4 containing 0.8 wt % cobalt were investigated. At pH 7 flatband potentials of -0.30 and +0.54 V vs NHE were measured for the bismuth vanadate and cobalt oxide, respectively, whereas -0.31 V was obtained for BiVO 4 /Co 3 O 4 . At a bias of 0.1 V vs Ag/AgCl the n-type photocurrent of BiVO 4 changes to p-type upon prolonged irradiation, whereas it remains n-type at the much hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
215
0
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 355 publications
(239 citation statements)
references
References 55 publications
15
215
0
9
Order By: Relevance
“…Calcination of this film at 573-723 K for 2 h in air gave a yellow BiVO 4 thin film. Cobalt oxide cocatalyst was loaded on the BiVO 4 film with an area of 2.5 cm 2 by an impregnation method with calcination at 673 K for 1 h in air using an aqueous solution (5 μL, 80 mmol L −1 ) of CoðNO 3 Þ 2 (Wako Pure Chemical; 99.5%), if necessary (17,18).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Calcination of this film at 573-723 K for 2 h in air gave a yellow BiVO 4 thin film. Cobalt oxide cocatalyst was loaded on the BiVO 4 film with an area of 2.5 cm 2 by an impregnation method with calcination at 673 K for 1 h in air using an aqueous solution (5 μL, 80 mmol L −1 ) of CoðNO 3 Þ 2 (Wako Pure Chemical; 99.5%), if necessary (17,18).…”
Section: Methodsmentioning
confidence: 99%
“…Development of a photoelectrode material with visible light response has been sought for efficient utilization of solar energy. It has been reported that Fe 2 O 3 (9-11), WO 3 (12)(13)(14), BiVO 4 (15)(16)(17)(18)(19)(20)(21)(22)(23)(24), and SrTiO 3 ∶Rh (25) of metal oxide electrodes respond to visible light. Recently, some (oxy) nitride materials such as TaON (26,27), Ta 3 N 5 (27,28), SrNbO 2 N (29), and Ta 0.9 Co 0.1 N x (30) have also been found to be visible light responsive photoelectrodes for water splitting.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we prepared Co-doped BiVO 4 using the amorphous heteronuclear complexation technique. The heteronuclear complex precursor is stable and its chemical composition is easy to control comparing with that prepared by other methods such as solidstate reaction [28], sol-gel [29], coprecipitation [30], metalorganic decomposition [31], and solution combustion [32]. Furthermore, the crystallization step can be readily controlled at low calcination temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the tetragonal BiVO 4 possesses a band gap of 2.9 eV and mainly absorbs UV region, while the monoclinic clinobisvanite (m-BiVO 4 ) exhibits a much higher photocatalytic activity due to its ideal band gap (2.4−2.5 eV) which absorb the UV and visible regions of the electromagnetic spectrum, having an ideal valence band edge position for driving water oxidation [9]. However, it has been recently reported that m-BiVO 4 , an n-type semiconductor [10], exhibits poor photocatalytic property which is stem to low mobility of the photogenerated charge carriers (electron−hole pairs), positive potential of CB (vs NHE) and high charge recombination rates which significantly limit its practical applications. The photocatalytic activity of m-BiVO 4 can be tuned either with metal or non-metal doping, semi-conductor recombination (heterojunction formation), depositing the co-catalysts, defect formation (oxygen vacancy creation), and crystal-facet control or morphological modification.…”
Section: Introductionmentioning
confidence: 99%